2006
DOI: 10.1111/j.1572-0241.2006.00481.x
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Candidate Genotypes Associated with Dyspepsia in a U.S. Community

Abstract: Meal-unrelated dyspepsia in a U.S. community study is associated with the homozygous 825T or C alleles of GNbeta3 protein. Candidate genes controlling adrenergic, serotonergic, and CCKergic functions do not appear to be associated with dyspepsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
122
3
8

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(136 citation statements)
references
References 58 publications
2
122
3
8
Order By: Relevance
“…In one study 118 of polymorphisms in candidate genes for different 5-HT receptors, cholecystokinin receptors and GNB3 as well as in the promoters of the genes encoding cholecystokinin and the sodium-dependent serotonin transporter, only the role of GNB3 in functional dyspepsia was confirmed.…”
Section: Genetic Contributionsmentioning
confidence: 99%
“…In one study 118 of polymorphisms in candidate genes for different 5-HT receptors, cholecystokinin receptors and GNB3 as well as in the promoters of the genes encoding cholecystokinin and the sodium-dependent serotonin transporter, only the role of GNB3 in functional dyspepsia was confirmed.…”
Section: Genetic Contributionsmentioning
confidence: 99%
“…There are also several studies that have pointed out significant associations between SERT polymorphism and IBS [29][30][31][32][33] . To our knowledge, the only result that confirms the relevance of SERT polymorphisms in relation to dyspeptic symptoms comes from studies of postprandial distress syndrome [8] , while at least two other investigations failed to detect significant associations [34][35][36][37] . Gene expression levels have previously been described in dyspeptic female patients [7] , where decreased SERT expression was found in the patient group.…”
Section: Discussionmentioning
confidence: 95%
“…It was observed that IL-17 and migratory inhibitory factor (MIF) have an important role in the inflammatory response to H. pylori and may affect the development of functional dyspepsia in H. pylori infected subjects but there was no association of 779TC of CCK-1 intron 1 polymorphism with functional dyspepsia in US community [25]. Similarly 1676T allele carriers of cyclooxygenase-1 (cox-1) was associated with developing gastric ulcer but not associated with functional dyspepsis [27].…”
Section: Genetics Aspect Of Functional Dyspepsiamentioning
confidence: 92%
“…The association between SERT polymorphism and functional dyspepsia was explored in two studies; however they showed no significant association between them [25,26]. It was observed that IL-17 and migratory inhibitory factor (MIF) have an important role in the inflammatory response to H. pylori and may affect the development of functional dyspepsia in H. pylori infected subjects but there was no association of 779TC of CCK-1 intron 1 polymorphism with functional dyspepsia in US community [25].…”
Section: Genetics Aspect Of Functional Dyspepsiamentioning
confidence: 99%